2011
DOI: 10.1016/j.immuni.2011.03.014
|View full text |Cite
|
Sign up to set email alerts
|

B7-H2 Is a Costimulatory Ligand for CD28 in Human

Abstract: SUMMARY CD28 and CTLA-4 are cell surface cosignaling molecules essential for the control of T cell activation upon the engagement of their ligands, B7-1 and B7-2 from antigen-presenting cells. By employing a newly developed receptor array, we have demonstrated that B7-H2, best known as the ligand of Inducible Costimulator, was a ligand for CD28 and CTLA-4 in human, whereas these interactions were not conserved in mouse. B7-H2 interacted with CD28 in a non-overlapping domain as B7-1 and B7-2, and was essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 33 publications
2
122
1
Order By: Relevance
“…In summary, the optimal elaboration of secondary CD8 ϩ T E responses in the LCMV Arm model requires CD8 ϩ T M -expressed CD28 but surprisingly not host-expressed CD80/86. The most straightforward explanation for this unexpected phenomenon is the existence of a novel CD28 ligand in addition to CD80/86, and while investigations to this extent are currently ongoing, we note that a very recent report documented a new CD28 ligand, the B7 family member ICOSL/B7-H2, in humans but apparently not in mice (83).…”
Section: Cd80mentioning
confidence: 73%
See 2 more Smart Citations
“…In summary, the optimal elaboration of secondary CD8 ϩ T E responses in the LCMV Arm model requires CD8 ϩ T M -expressed CD28 but surprisingly not host-expressed CD80/86. The most straightforward explanation for this unexpected phenomenon is the existence of a novel CD28 ligand in addition to CD80/86, and while investigations to this extent are currently ongoing, we note that a very recent report documented a new CD28 ligand, the B7 family member ICOSL/B7-H2, in humans but apparently not in mice (83).…”
Section: Cd80mentioning
confidence: 73%
“…5C versus 8B]), we have now obtained functional in vivo evidence that CD8 ϩ T M may productively interact with a novel CD28 ligand. In humans, such a ligand was recently identified (ICOSL/B7-H2), and while CD28-ICOSL interactions appear not to take place mice (83), it is not unreasonable to consider the possibility of other murine CD28 ligands among known or novel B7 family members (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…144 This was the same molecule, ICOS-ligand (B7RP-1/B7h/ ICOS-L/CD275), and a later study showed that ICOS-L could bind and costimulate via CD28. 145 ICOS may play a role in maintaining durable immune reactions 146 and is expressed at particularly high levels in germinal center T cells or TFH (follicular helper) cells. 147,148 ICOS-L is constitutively expressed by APCs as well as diverse nonhematologic tissues 143 and down-regulated with ongoing inflammation, 149,150 in contrast to the activation-induced CD28 ligands CD80/CD86.…”
Section: Another Costimulatory B7 Pathway: Icos and B7-h2mentioning
confidence: 99%
“…For comparison, the potency of abatacept, which blocks the CD28 pathway indirectly by binding to CD80 and CD86 molecules on the APC, is ∼2300 ng/ml (25 nM) in T cell proliferation (Table II). It has been reported that CD28 can also bind to ICOS ligand on APCs and act as a costimulus, with suboptimal concentrations of anti-CD3 mAb, to promote T cell proliferation (32). In assays in which suboptimal concentrations of immobilized anti-CD3 and ICOS ligand were coimmobilized at either 10 or 30 mg/ml, anti-CD28 dAb, at concentrations well above the IC 90 for inhibition of a DC-MLR, was unable to inhibit this response (data not shown).…”
Section: In Vitro Characterizationmentioning
confidence: 99%